Correlation of unipolar electrogram modification with ablation index during pulmonary vein isolation: A pilot study. Issue 2 (20th December 2022) - Paymard, Mohammad; Deyell, Marc W.; Laksman, Zachary W.; Yeung‐Lai‐Wah, John A.; Chakrabarti, Santabhanu
Abstract: Background: Pulmonary vein isolation (PVI) using radiofrequency catheter ablation is a widely accepted therapy for drug‐refractory atrial fibrillation patients. Elimination of the negative component of the local unipolar electrogram (UEGM) during PVI is a marker of transmural lesion formation. The ablation index (AI) can predict the quality of ablation lesion. Combining these two parameters could make PVI safer and efficient. The purpose of this pilot study was to examine the correlation between UEGM modification characteristics of the different target areas of left atrium and the associated AI values during PVI. Methods: We analyzed 10 patients who underwent PVI using radiofrequency energy. The local electrophysiological properties and ablation parameters of 15 designated areas of interest in the left atria targeted by radiofrequency catheter ablation were collected. Results: Out of the 10 patients, six were men (mean age 66 years) and 80% had paroxysmal AF. The mean time to achieve the UEGM modification in the posterior wall was shorter than that of the anterior wall (8.9 seconds vs. 11.1 s, respectively). The UEGM modification for every lesion was achieved at significantly lower AI values than conventional AIs ( p  < .001). Conclusion: During PVI, the AIs deduced according to the local UEGM modification are markedly shorter than those generally recommended AIs in contemporary practice. This indicates that conventionally recommended AIs could be safely reduced while ensuring the efficacy and quality of radiofrequency ablation during PVI. This approach would probably reduce to risk of collateral thermal injuries.